Peningkatan Akses Pembelajaran Melalui Aplikasi Mobile Learning Berbasis Thunkable bagi Siswa SMP Kelurahan Klawalu Kota Sorong - Melda Agnes Manuhutu; Sherly Gaspersz; Lulu Jola Uktolseja; Imanuel Imanuel; Rosina Rosina; Selpius Selpius; Junius Junius; Rudi Rudi; Korneles Korneles; Rahma Rahma (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2025)
The integration of digital technology in education serves as a strategic solution to enhance learning access, particularly for students in regions with limited educational infrastructure, such as Sorong City, Southwest Papua. This community service program was designed to introduce and provide training to junior high school students in the use of the Thunkable application as a tool for mobile-based learning media. Thunkable is a visual drag-and-drop platform that enables users to design functional mobile applications without the need for prior programming knowledge. The method employed in this activity is based on the Research and Development (R&D) approach using the 4D model, which consists of four stages: Define, Design, Develop, and Disseminate. In the Define stage, the needs and digital readiness of the target group were assessed. The Design and Develop stages involved creating a training module and conducting hands-on workshops where students were guided step-by-step to create simple educational apps. In the final Disseminate stage, the outcomes were evaluated and shared for broader use. The results of this initiative revealed high levels of enthusiasm among the participants. Students were actively engaged and demonstrated the ability to independently design simple learning applications by the end of the training. This indicates that the use of Thunkable not only increases students' digital literacy but also enhances their self-directed learning, creativity, and technological confidence. Overall, this activity illustrates the potential of mobile learning tools to support inclusive and adaptive education in remote communities. By equipping students with practical digital skills, it lays the foundation for long-term educational innovation and empowerment. Therefore, the use of Thunkable can be considered an effective and accessible alternative to foster meaningful learning experiences across diverse educational contexts.